Exploring the role of N-acetyltransferases in diseases: a focus on N-acetyltransferase 9 in neurodegeneration - Prajakta Deshpande; Anuradha Venkatakrishnan Chimata; Amit Singh (Neural Regeneration Research)
Acetyltransferases, required to transfer an acetyl group on protein are highly conserved proteins that play a crucial role in development and disease. Protein acetylation is a common post-translational modification pivotal to basic cellular processes. Close to 80%–90% of proteins are acetylated during translation, which is an irreversible process that affects protein structure, function, life, and localization. In this review, we have discussed the various N-acetyltransferases present in humans, their function, and how they might play a role in diseases. Furthermore, we have focused on N-acetyltransferase 9 and its role in microtubule stability. We have shed light on how N-acetyltransferase 9 and acetylation of proteins can potentially play a role in neurodegenerative diseases. We have specifically discussed the N-acetyltransferase 9-acetylation independent function and regulation of c-Jun N-terminal kinase signaling and microtubule stability during development and neurodegeneration.